2015
DOI: 10.1016/j.procs.2015.05.036
|View full text |Cite
|
Sign up to set email alerts
|

DSM: Dynamic Sink Mobility Equipped DBR for Underwater WSNs

Abstract: In this paper, we present Dynamic Sink Mobility equipped DBR (DSM) routing protocol for Underwater Wireless Sensor Networks (UWSNs). Our proposed scheme increases the stability period, network lifetime, and throughput of the UWSN. The scheme incorporates dynamic sink mobility in a way that sink moves towards most dense (in terms of number of nodes) region (quadrant) of the network. Moving the sink to high density region ensures maximum collection of data. As, more number of nodes (sensors) are able to send dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…We took into consideration the underwater environment and all the necessary equations and coefficients for underwater channel. 10,20 Figure 2 shows a sample screen F I G U R E 2 A sample screen from our simulator with a network of 500m × 500m × 500m divided into four layers with 10 × 10 grid size of our simulator representing a network with a size of 500m × 500m × 500m divided into four layers, a 10 × 10 grid size and with settings that can be adjusted. Data packet size is set to 64 bytes while the control packet size is set to 4 bytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We took into consideration the underwater environment and all the necessary equations and coefficients for underwater channel. 10,20 Figure 2 shows a sample screen F I G U R E 2 A sample screen from our simulator with a network of 500m × 500m × 500m divided into four layers with 10 × 10 grid size of our simulator representing a network with a size of 500m × 500m × 500m divided into four layers, a 10 × 10 grid size and with settings that can be adjusted. Data packet size is set to 64 bytes while the control packet size is set to 4 bytes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been focused on achieving this by considering one or more optimization metrics. A dynamic sink mobility (DSM) technique presented by Khan et al 20 was shown to enhance the network lifetime. Authors assumed nodes are deployed in a 2D region where the network topology is partitioned into four regions (quadrants).…”
Section: Auv Path Planning For Data Collectionmentioning
confidence: 99%
“…Based on the routing strategy and the major parameters it utilizes for routing purposes, UASN routing can be classified into reliable data forwarding protocols (Nicolaou et al, 2007;Yan et al, 2008;Ayaz and Abdullah, 2009;Wahid et al, 2014;Noh et al, 2016) and predication-based data forwarding protocols (Ayaz and Abdullah, 2009;Wahid and Kim, 2012;Chen and Lin, 2013;Jafri et al, 2013;Wei et al, 2013;Jafri et al, 2014;Khan et al, 2015;Umar et al, 2015).…”
Section: Related Workmentioning
confidence: 99%
“…The vehicle moves through the stations following the path generated by the base layer, where on-time visit to the target station is the main concern of this layer. The UUV broadcast its position in the map to the closest sink, as they get visited [15]. By doing so, the other sensors associate their regions with the UUV.…”
Section: A Underwater Wireless Sensor Network (Uwsn) Integration and ...mentioning
confidence: 99%
“…The local path generated by the inner layer gets evaluated by the path time (proportional to energy consumption and travelled distance) and its collision avoidance capability. It should be feasible and meet the environmental and vehicle kinematic constraints (described by (15)). The environmental constraints are associated with coastal area of map and fixedmobile obstacles; and the kinematic constraints associated with UUV's yaw surge and sway rates.…”
Section: B Multilayered Motion Planning Optimization Criterionmentioning
confidence: 99%